2,5-Dimethylphenacyl carbamate: a photoremovable protecting group for amines and amino acids - Kammari, Laxminarayana; Plístil, Lukás; Wirz, Jakob; Klán, Petr (Photochemical & photobiological sciences, 2007)
2,5-Dimethylphenacyl (DMP) carbamates (1a-c) released the corresponding free amines or amino acids in high chemical yields, albeit with quantum yields Phi of only 0.04-0.09, upon irradiation in either aprotic or protic solvents. The photoreaction proceeded principally from the triplet excited state via the E-photoenol. The lifetimes of the triplet enol and the E- and Z-enols in the ground state were determined by laser flash photolysis. The primary photoinitiated transformation liberated a carbamic acid derivative, which subsequently decarboxylated to the amino group-containing compound. Exhaustive irradiation of a DMP-protected aniline (1a) in acetonitrile did not provide aniline in quantitative chemical yields, because it was involved in reductive cleavage of the starting material as an electron donor, thereby decreasing the overall deprotection yield (86%). Phenylalanine methyl ester, liberated from 1c, was, however, obtained in excellent chemical yield (97%). It was also found that the carbamates, while thermally stable, released amines with higher quantum yields in acidic methanol solutions. The DMP chromophore is proposed as an excellent photoremovable protecting group for amino acids and, under specific conditions, for amines in organic synthesis and biochemistry.
Keywords: Carbamates; karbamáty; molekulární struktura; aminy; Amino Acids; Amines; Photochemistry; fotochemie; aminokyseliny; Molecular Structure